THE Community Outreach on Alternative Energy from New and Renewable Energy Sources through Appropriate Technology for the Residents of Sawah Lebar Baru Subdistrict, Ratu Agung District, Bengkulu City - Angky Puspawan; Agustin Gunawan; A Sofwan FA; Afdhal Kurniawan Mainil; Alex Surapati; Fepy Supriani; Hardiansyah Hardiansyah; Helmizar Helmizar; Nurul Iman Supardi; Zuliantoni Zuliantoni (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2026)
The increasing demand for energy, driven by population growth and economic activities, necessitates the utilization of sustainable alternative energy sources. New and Renewable Energy (NRE) has become one of the key solutions to reduce dependence on depleting fossil fuels, which also have negative impacts on the environment. This community service activity aims to enhance public knowledge and understanding of alternative energy utilization based on NRE through the application of appropriate technology. The methods employed include community outreach, educational sessions, and simple demonstrations of alternative energy technologies. The activity was conducted in Sawah Lebar Baru Subdistrict, Ratu Agung District, Bengkulu City, which is one of the two assisted areas of the Faculty of Engineering, University of Bengkulu. The results indicate an improvement in community understanding of alternative energy concepts as well as an increased interest in adopting simple technologies such as biogas, biomass, and solar energy. Therefore, this activity is expected to promote community energy independence and resilience, support sustainable development at the local level, and contribute to the government’s national energy security program.